CONTEXTUALIZATION AND CONNECTIVITY OF DIGITAL LITERACY IN PRIMARY SCHOOL SOCIAL STUDIES DURING THE COVID-19 PANDEMIC - Siti Kowiyah; Yatim Riyanto; Harmanto Harmanto (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Riau, 2021)
This research identifies and explores Social Science (IPS) learning at the Elementary School level (SD) delivered by utilizing digital technology during the Covid-19 pandemic in Indonesia. This study explores the use of the internet and how social knowledge learning is in dialogue with digital literacy that occurs in it. This research is a qualitative study of digital literacy in social studies learning in elementary schools. The data sources were elementary school teachers using random sampling, with spatial boundaries in Surabaya and Sidoarjo, East Java. The temporal limitation of this research is data taken from April 2020 to January 2021. The collected data is then analyzed with Kathleen Tyner's perspective regarding literacy in the digital world and June Chapin about social studies learning in primary education. The results showed that contextuality and connectivity through digital literacy in elementary social studies raise constructive aspects through collective memory about experiencing something and using previous knowledge through digital literacy. The constructive and cognitive aspects present two essential dimensions that explain the occurrence of elementary social knowledge learning. First, relating to information processing; in terms of receiving, storing, and then remembering information when it has needed. Second, related to meaningful learning about social life in society, how children shape and organize existing and new information that comes to mind. Therefore, this model can teach and study any subject matter related to social studies at the elementary school level.